2014
DOI: 10.11648/j.jfns.20140201.12
|View full text |Cite
|
Sign up to set email alerts
|

Fast Food Consumption Drift in Pakistani Population

Abstract: Objective: To appraise the use of various fast foods in different age groups among males and females and study its drift in Pakistani population. Method: The study was conducted from February to June 2013 in Karachi, Pakistan on a structured questionnaire. A total of n=489 individuals participated in this study among which n= 222 were males and n= 267 were females whose ages were grouped as <18 years, 18-40 years and >40 years. Fast food was categorized as fries, burgers, rolls, chicken broast and pizza wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Health consciousness is health/nutrition awareness and knowledge which refers to the degree of readiness to undertake health actions (Becker and Maiman, 1975) that influence health attitudes and behaviors (Iversen and Kraft, 2006). As mentioned previously, health consciousness has a prominent effect on consumers’ attitudes (Jahan et al , 2014). Therefore, this factor was assessed in this study using four-scale items, including: “I do not want to eat fast-food because it has high calories,” “I do not want to eat fast-food as its consumption causes an imbalance in weight,” “I do not want to use fast-food as it can be one of the reasons for high cholesterol,” and “I do not want to eat fast-food because it has a lot of preservatives.” Participants rated their agreement to each item on a five-point scale (ranging from “1: fully disagree” to “5: fully agree”).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Health consciousness is health/nutrition awareness and knowledge which refers to the degree of readiness to undertake health actions (Becker and Maiman, 1975) that influence health attitudes and behaviors (Iversen and Kraft, 2006). As mentioned previously, health consciousness has a prominent effect on consumers’ attitudes (Jahan et al , 2014). Therefore, this factor was assessed in this study using four-scale items, including: “I do not want to eat fast-food because it has high calories,” “I do not want to eat fast-food as its consumption causes an imbalance in weight,” “I do not want to use fast-food as it can be one of the reasons for high cholesterol,” and “I do not want to eat fast-food because it has a lot of preservatives.” Participants rated their agreement to each item on a five-point scale (ranging from “1: fully disagree” to “5: fully agree”).…”
Section: Methodsmentioning
confidence: 89%
“…Mattsson and Helmersson (2007) concluded that Swedish high school students generally have information about all aspects of fast-food, meaning that they possess awareness of the negative side effects of fast-food, and accordingly pay more attention to nutritional and health concerns than price, speed, and convenience. Jahan et al (2014) conducted a study among Pakistan consumers, showing that frequent fast-food consumption can be influenced via health consciousness of fast-food. Others have studied the relationship between subjective norm and rate of fast-food consumption, concluding that subjective norms is one of the important factors that affect fast-food intake (Astrom and Rise, 2001; Bissonnette and Contento, 2001; Seo et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…8,[13][14][15] While this cancer has traditionally been prevalent in developed countries, its high prevalence in Pakistan is alarming and may have been caused by increasing adaptation to westernized diet and life style in Pakistan. 23 We report non melanoma skin cancers (NMSCs) amongst the top cancers in both genders in Karachi. Since Karachi is located nearer to the equator (latitude 24.8 º N and longitude 67.1 o E) as compared to other parts of Pakistan, it is possible that its proximity to the equator imposes higher risk of developing skin cancers in Karachi.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 13 - 15 While this cancer has traditionally been prevalent in developed countries, its high prevalence in Pakistan is alarming and may have been caused by increasing adaptation to westernized diet and life style in Pakistan. 23 …”
Section: Discussionmentioning
confidence: 99%
“…This cancer is thought to be historically more common in western population whose diet is rich in fat and red meat and low in fiber (Yaha et al, 2013). This is alarming and points an adversity of globalization with increasing consumption of fast and junk food including smoked red meat (Jahan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%